2012
DOI: 10.1111/j.1600-0714.2012.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan‐1 (CD 138) surface expression marks cell type and differentiation in ameloblastoma, keratocystic odontogenic tumor, and dentigerous cyst

Abstract: J Oral Pathol Med (2013)42: 186–193 Background:  The altered expression of syndecan‐1 (SD‐1), a transmembrane heparan sulfate proteoglycan, in ameloblastomas and cysts of odontogenic origin suggests that this molecule could have prognostic value in assessing the clinical outcome of those lesions. The purpose of this study was to analyze SD‐1 expression profile immunohistochemically in archival, paraffin‐embedded tissue sections of ameloblastomas and in common odontogenic cysts arising from the same locale. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 34 publications
(42 reference statements)
4
31
2
Order By: Relevance
“…However, it has been demonstrated that CD138 is expressed by the stromal cells in the some neoplastic and non-neoplastic odontogenic lesions (ameloblastoma, KCOT and DC), and ovarian cancers, as well as plasma cells (24,33). It has also been stated that the expression of CD138 is associated with poor prognosis (24,33). CD138 (syndecan 1) shifting from epithelium to stroma was reported in invasive non-odontogenic solid tumors including breast, prostate, lung, and colon cancers (21).…”
Section: Some Authors Suggested That Loss Of E-cadherin Expression Inmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has been demonstrated that CD138 is expressed by the stromal cells in the some neoplastic and non-neoplastic odontogenic lesions (ameloblastoma, KCOT and DC), and ovarian cancers, as well as plasma cells (24,33). It has also been stated that the expression of CD138 is associated with poor prognosis (24,33). CD138 (syndecan 1) shifting from epithelium to stroma was reported in invasive non-odontogenic solid tumors including breast, prostate, lung, and colon cancers (21).…”
Section: Some Authors Suggested That Loss Of E-cadherin Expression Inmentioning
confidence: 99%
“…Although there are several studies related to role of these proteins in odontogenic lesions in English literature (8,9,18,24,(27)(28)(29), no comparative and comprehensive study, in which the expression of these proteins or adhesion molecules in odontogenic cystic lesions have been evaluated, to our knowledge. Therefore, we aim to evaluate the immunohistochemical expressions of CD138 (syndecan-1), CD38, E-cadherin and survivin in these cystic odontogenic lesions and investigate the potential implications of their expressions among these lesions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] Al-Otaibi et al, (2013) studied SDC-1 immunoreactivity in the stromal cells of AB, keratocystic odontogenic tumor (KCOT), and dentigerous cysts and it was suggested that the SDC-1 expression by the tumor stroma is considered to be associated with poor prognosis of the lesions. [7] Heikinheimo et al, (1991) stated that there is an association between the stronger labeling of α5β1 integrin in the neoplastic cells of ABs and greater migration capacity of these cells because of increased fi bronectin expression in stromal cells. [8] Later, Souza Andrade et al, (2007) studied the role of α5β1 integrin in AB, adenomatoid odontogenic tumor (AOT), and proposed that the mechanism of tumor invasion might be because of α5β1 integrin binding to fi bronectin which in turn increases the secretion and expression of metalloproteinases.…”
Section: Clonalitymentioning
confidence: 99%